Ferroelectric phase transition and impurity-lattice correlations in Pb1-XGeXTe(Ga) - Achimov, B. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2006)
The impedance of single-crystal samples of PbTe(Ga) and Pb1-XGeXTe(Ga) (0≤x≤0.095)